Transforming Household Waste into Educational Play Tools: A Sustainable Approach to Early Childhood Education - Dewi Maya Sari; Zulfan; Lindawati; Dinda Dwi Abelia; Raina Salsabila; Mufti Miadi Ghufran S.; Erdiansyah Rahmi (Altifani Journal: International Journal of Community Engagement, 2024)
This program aims to enhance the skills of Early Childhood Education (ECE) teachers in Syiah Kuala District by utilizing household waste as a basis for Educational Play Tools (EPT). Implemented through training sessions, the program includes EPT creation materials, waste processing techniques, and guidance to design creative and functional tools. The results indicate a significant increase in participants' understanding and ability to process household waste into safe, engaging educational tools for children. The impact is evident from increased teacher creativity and active participation in using waste as environmentally friendly learning media. This program contributes to household waste management and enriches ECE teaching methods in the area.